2017
DOI: 10.1136/bmjopen-2016-012856
|View full text |Cite
|
Sign up to set email alerts
|

Causes of and contributors to infant mortality in a rural community of North India: evidence from verbal and social autopsy

Abstract: ObjectiveTo identify the medical causes of death and contribution of non-biological factors towards infant mortality by a retrospective analysis of routinely collected data using verbal and social autopsy tools.SettingThe study site was Health and Demographic Surveillance System (HDSS), Ballabgarh, North IndiaParticipantsAll infant deaths during the years 2008–2012 were included for verbal autopsy and infant deaths from July 2012 to December 2012 were included for social autopsy.Outcome measuresCause of death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
3
23
2
2
Order By: Relevance
“…In the present study, 11.6% of neonates died during followup. We found that most of the deaths occurred during the first (34.0%) and second (61.3%) weeks of neonatal life, which were in line with the previous systematic review studies [7,8] and the studies done in India [32] and Tanzania [33] and also the studies done in Ethiopia [10,[22][23][24].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, 11.6% of neonates died during followup. We found that most of the deaths occurred during the first (34.0%) and second (61.3%) weeks of neonatal life, which were in line with the previous systematic review studies [7,8] and the studies done in India [32] and Tanzania [33] and also the studies done in Ethiopia [10,[22][23][24].…”
Section: Discussionsupporting
confidence: 90%
“…death registers). In the absence of such systems, in LMICs, verbal autopsies are commonly used to ascertain the underlying and immediate CoD among specific populations of both children and adults . However, population level mortality and/or verbal autopsy data are not routinely available for children with CP in LMICs such as Bangladesh.…”
mentioning
confidence: 99%
“…Deaths due to LBW/ prematurity were mostly due to delay in identification of danger signs and decision making to seek care. (4) About 0.75 million neonates die in India every year, the highest for any country in the world. The rate of decline in NMR and to some extent EMNR has accelerated with the introduction of National Rural Health Mission in mid 2005.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Also it has been seen that delay in identification of danger signs, delayed decision to seek care and absence of health personnel during transport and referral had significant correlation with mortality. (3,4) In order to further bring down the neonatal and infant mortality and to bridge the urban rural gap it is imperative to shift the focus of neonatal research to the peripheral level health facilities and understand the challenges posed by the socio-demographic profile of the populations in these areas.…”
Section: Introductionmentioning
confidence: 99%